2013
DOI: 10.4067/s0718-07642013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivación Térmica de Pectinmetilesterasa en Tomate de Árbol (Solanum betaceum)

Abstract: * Autor a quien debe ser dirigida la correspondenciaRecibido Nov. 22, 2012; Aceptado Ene. 08, 2013; Versión final recibida Mar. 05, 2013 Resumen El objetivo de esta investigación fue estudiar el efecto del procesamiento térmico a temperatura constante, sobre la actividad residual de la enzima pectinmetilesterasa (PME), causante de la separación de fases en néctar de tomate de árbol (Solanum betaceum). Se evaluó un rango de temperaturas entre 40 y 90°C y tiempos de exposición entre los 5 y 20s. La actividad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The juice was obtained in a FMC extractor, FS BR 1 model (Brasil), and filtered through ASTM#18 sieves. The volume was divided in two fractions: one was reserved as "natural juice" (JN); the other was pasteurized (JP) to reduce native flora that could compete with inoculated yeasts during alcoholic fermentation, as well as to inactivate the pectinmethilesterase (PME) enzyme that could affects juice stability (Dsorio et al, 2008;Maca et al, 2013). Heat treatment was performed at 90ºC for 30 s in a Figmay shell and tube heat exchanger (Argentina).…”
Section: Orange Juice Extractionmentioning
confidence: 99%
“…The juice was obtained in a FMC extractor, FS BR 1 model (Brasil), and filtered through ASTM#18 sieves. The volume was divided in two fractions: one was reserved as "natural juice" (JN); the other was pasteurized (JP) to reduce native flora that could compete with inoculated yeasts during alcoholic fermentation, as well as to inactivate the pectinmethilesterase (PME) enzyme that could affects juice stability (Dsorio et al, 2008;Maca et al, 2013). Heat treatment was performed at 90ºC for 30 s in a Figmay shell and tube heat exchanger (Argentina).…”
Section: Orange Juice Extractionmentioning
confidence: 99%
“…El pH promedio de los jarabes de agave azul es de 4, algunas muestras son mayor (4,4) y menor (3,69). El pH del jarabe de agave azul indicado en la Norma mexicana es de 4 a 6; varias de las muestras analizadas no cumplieron con la normatividad pues su pH fue menor, pero sus valores coinciden con el reportado por López, Vera-Guzmán, & Mellado-Mojica (2011). El pH del jarabe de agave azul frecuentemente es cercano a 4 (Mellado-Mojica & López-Pérez, 2013), frente al valor reportado en el presente estudio.…”
Section: Caracterización Fisicoquímicaunclassified
“…This decrease in enzyme activity was explained by the denaturation of the enzyme. On the other hand, Maca et al [16] showed that drying at high temperatures influenced the enzymatic activity of pectinmethylesterase in Tree Tomatoes (Solanum betaceum), by determining that there was a 28% decrease in the concentration of product formed by increasing the drying temperature from 60 °C to 90 °C.…”
Section: Table 1 Enzymatic Activity Values (Ea) Linear Regression Coe...mentioning
confidence: 99%